2003
DOI: 10.1111/j.1944-8287.2003.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberal Policy and Deforestation in Southeastern Mexico: An Assessment of the PROCAMPO Program

Abstract: A lingering question in economic geography is the degree to which there is a link between neoliberal policies and environmental degradation. Research is needed to relate such policies empirically to local‐level decision making, both to evaluate their consequences and to contribute to an understanding of how cross‐scalar dynamics drive processes of land‐use change. This study examines the environmental impacts of a Mexican rural support program, referred to by its Spanish acronym, PROCAMPO, which was introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 21 publications
3
86
0
4
Order By: Relevance
“…Researchers measured an increase in deforestation carried out by PROCAMPO recipients ranging from 6.5% to 38%, observing that Yucatán farmers used their PROCAMPO-supported lands to grow cash crops, such as Chili peppers, while subsistence crops like maize and beans were shifted to newly cleared fields. These findings provide support for broader analyses suggesting that, under economic liberalization policies, smallscale farmers' limited access to credit and purchased inputs makes it difficult for them to undertake intensification using existing agricultural resources (Klepeis and Vance 2003;Shriar 2002;Barbier 2000). These behavioral patterns are relevant to the discussion of in situ conservation 5 Initially, under the administration of Ernesto Zedillo (1994Zedillo ( -2000 these programs were introduced as Alianza para el campo.…”
Section: Structural Changes In Post-nafta Policymentioning
confidence: 73%
See 2 more Smart Citations
“…Researchers measured an increase in deforestation carried out by PROCAMPO recipients ranging from 6.5% to 38%, observing that Yucatán farmers used their PROCAMPO-supported lands to grow cash crops, such as Chili peppers, while subsistence crops like maize and beans were shifted to newly cleared fields. These findings provide support for broader analyses suggesting that, under economic liberalization policies, smallscale farmers' limited access to credit and purchased inputs makes it difficult for them to undertake intensification using existing agricultural resources (Klepeis and Vance 2003;Shriar 2002;Barbier 2000). These behavioral patterns are relevant to the discussion of in situ conservation 5 Initially, under the administration of Ernesto Zedillo (1994Zedillo ( -2000 these programs were introduced as Alianza para el campo.…”
Section: Structural Changes In Post-nafta Policymentioning
confidence: 73%
“…A study of deforestation on the Yucatán peninsula (Klepeis and Vance 2003) suggests that the availability of PRO-CAMPO led to increasing levels of deforestation in the post-NAFTA period. Researchers measured an increase in deforestation carried out by PROCAMPO recipients ranging from 6.5% to 38%, observing that Yucatán farmers used their PROCAMPO-supported lands to grow cash crops, such as Chili peppers, while subsistence crops like maize and beans were shifted to newly cleared fields.…”
Section: Structural Changes In Post-nafta Policymentioning
confidence: 99%
See 1 more Smart Citation
“…A complex pattern of livelihood strategies also occurs in the southern region of the Yucatán Peninsula, including subsistence maize, commercial chili cultivation, wage labor, pasture production, and conservation land uses such as harvest of non-timber forest products (Chowdhury 2010, Dalle et al 2011. The hierarchical system of distribution that was implemented in the southern cone of the state of Yucatán as a result of a neoliberal federal policy also reveals the connections between local markets and global agricultural production, as does the increase in commercial chili pepper production in Campeche (Keys 2004, Klepeis & Vance 2003.…”
Section: Discussionmentioning
confidence: 99%
“…For example based on survey data from 1986-1997, Programa de Apoyos Directos al Campo (PRO-CAMPO), an agricultural program implemented in 1994 with the goal of integrating agricultural markets and intensifying production, revealed only modest increases in market production, but an increase in deforestation occurred through the conversion of land to commercial chili production and pastures (Klepeis & Vance 2003). A study based on household surveys carried out in 1997 and 2003 found that similar land use choices were being made by some, although others were choosing to withdraw from agriculture all together and those who converted their land to pasture or commercial agriculture were using less land than previously devoted to extensive agricultural practices, resulting in a decrease in deforestation (Busch & Geoghegan 2010, Radel et al 2010, Schmook & Radel 2008.…”
Section: Land Use/land Cover Change and Associated Drivers In The Yucmentioning
confidence: 99%